Visage—Visualization of algorithms in discrete mathematics - Geschke, Anne; Kortenkamp, Ulrich; Lutz-Westphal, Brigitte; Materlik, Dirk (ZDM, 2005)
Which route should the garbage collectors' truck take? Just a simple question, but also the starting point of an exciting mathematics class. The only “hardware” you need is a city map, given on a sheet of paper or on the computer screen. Then lively discussions will take place in the classroom on how to find an optimal routing for the truck. The aim of this activity is to develop an algorithm that constructs Eulerian tours in graphs and to learn about graphs and their properties.This teaching sequence, and those stemming from discrete mathematics, in particular combinatorial optimization, are ideal for training problem solving skills and modeling—general competencies that, influenced by the German National Standards, are finding their way into curricula.In this article, we investigate how computers can help in providing individual teaching tools for students. Within the Visage project we focus on electronic activities that can enhance explorations with graphs and guide studients even if the teacher is not available—without taking away freedom and creativity.The software package is embedded into a standard DGS, and it offers many pre-built and teacher-customizable tools in the area of graph algorithms.Until now, there are no complete didactical concepts for teaching graph algorithms, in particular using new media. We see a huge potential in our methods, and the topic is highly requested on part of the teachers, as it introduces a modern and highly relevant part of mathematics into the curriculum.